(untitled) (Journal of Medicine, 2008)
Fifty cases of hand trauma of different aetiology with soft tissue loss with exposed tendons and bones were treated in NITOR and DMCH, Dhaka between January ’97 and December ’02 with groin flap. Eighty three percent (83%) cases have good results with excellent flap adhesion and no flap loss. Seventeen percent (17%) cases have some degree of flap loss which were taken to be acceptable. Overall result in terms of restoring the hand function was encouraging which was approximately eighty eight percent (88%). Â DOI = 10.3329/jom.v7i1.1357 J MEDICINE 2006; 7 : 15-19